Pengembangan Model Konstruksi Sumur Resapan dalam Menurunkan BOD dan COD pada Air Limbah Rumah Tangga - Abdul Ganing; Zrimurti Mappau (Politeknik Kesehatan Kemenkes Mamuju, 2019)
The entry of domestic wastewater into the aquatic environment will result in major changes in the physical, chemical and biological properties of the waters such as temperature, turbidity, recruited oxygen concentration, nutrients, and production of toxic materials.The level and extent of the effect that is generated on these aquatic organisms is highly dependent on the type and amount of pollutants entering the waters. Changes in the balance between physical-chemical and biological factors in an environment due to the presence of polluting compounds that can affect organisms in that environment. One way to find out how far the pollution load on wastewater is by measuring BOD and COD. Efforts to process domestic waste (greywater) in a simple way, namely by processing aerobic and anaerobic biofilter. The purpose of this study is to develop a household wastewater treatment system with an infiltration well model. This type of research is experimental research with the method of one group post test. Analysis of laboratory tests conducted at the Mamuju Ministry of Health's Integrated Polytechnic Laboratory to determine the effectiveness of household wastewater treatment using the infiltration well construction model, in reducing BOD and COD levels. The wastewater treatment system with the approach of infiltration well construction model effectively decreases BOD by an average of 92.69% from the initial level of 287 mg/L to 20.97 mg/L and COD an average of 85.72% from the initial level of 562 mg/L to 80.25 mg/L. The results of the study were declared effective and fulfilled the quality standard requirements of PermenLHK No.P68 of 2008 concerning domestic waste quality standardsIt is recommended to do media types, and use variations in residence time.